2008
DOI: 10.1534/genetics.107.083808
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Cell Adhesion Molecule Sticks-and-Stones Reveals Multiple Redundant Functional Domains, Protein-Interaction Motifs and Phosphorylated Tyrosines That Direct Myoblast Fusion in Drosophila melanogaster

Abstract: The larval body wall muscles of Drosophila melanogaster arise by fusion of founder myoblasts (FMs) and fusion-competent myoblasts (FCMs). Sticks-and-Stones (SNS) is expressed on the surface of all FCMs and mediates adhesion with FMs and developing syncytia. Intracellular components essential for myoblast fusion are then recruited to these adhesive contacts. In the studies herein, a functional analysis of the SNS cytodomain using the GAL4/UAS system identified sequences that direct myoblast fusion, presumably t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 55 publications
(75 reference statements)
2
61
0
Order By: Relevance
“…Although a signal molecule that mediates transduction in fcms in either of the two fusion phases has not yet been identified, a detailed analysis of the rescue capacity of SNS deletion constructs showed that the cytoplasmic domain of SNS possesses multiple redundant domains (Kocherlakota et al, 2008). This finding further strengthens the notion that there are different signalling cascades at play.…”
Section: Fig 5 a Model For Furmas Expansion Cell Adhesion And Furmmentioning
confidence: 55%
See 1 more Smart Citation
“…Although a signal molecule that mediates transduction in fcms in either of the two fusion phases has not yet been identified, a detailed analysis of the rescue capacity of SNS deletion constructs showed that the cytoplasmic domain of SNS possesses multiple redundant domains (Kocherlakota et al, 2008). This finding further strengthens the notion that there are different signalling cascades at play.…”
Section: Fig 5 a Model For Furmas Expansion Cell Adhesion And Furmmentioning
confidence: 55%
“…Membrane vesiculation and breakdown, however, seem to be controlled by other factors, e.g., a so far unknown fusogene (a protein that fuses membranes). We strongly suggest the presence of co-ordinated pathways leading to fusion pore formation and expansion, and also due to the complexity of the intracellular domain of SNS, the presence of multiple pathways at least in fcms (Kocherlakota et al, 2008). Finally, to add weight to this notion, biochemical experiments have provided evidence to suggest that SNS interacts with Crk, a SH2-SH3 type of adaptor protein, and that Vrp1 mediates the formation of a Crk-Vrp1-WASP complex in fcms (Kim et al, 2007).…”
Section: Regulation Of Actin Polymerization During Myoblast Fusionmentioning
confidence: 82%
“…Sns is required on the surface of the FCMs (Bour et al, 2000) for their ability to recognize founder cells and myotubes. The FCMs can clearly migrate to sites of ectopically expressed Kirre or Rst (Ruiz-Gomez et al, 2000;Strunkelnberg et al, 2001), and Sns is essential for this behavior (Kocherlakota et al, 2008). These data suggest that Kirre and Rst can function as Sns-dependent attractants for the FCMs, and that signaling cascades downstream of Sns direct migration.…”
Section: Myoblast Migration Recognition and Adhesion In Drosophilamentioning
confidence: 99%
“…Homozygous mutant embryos were identified by the absence of β-galactosidase (Kocherlakota et al, 2008). Primary antibodies to Sns (Bour et al, 2000) (embryos, 1:200, sorted embryonic GCNs, 1:100, larval GCNs, 1:80), Kirre (Galletta et al, 2004) (embryos, 1: 200, sorted embryonic GCNs, 1:100, larval GCNs, 1:1000) anti-β-galactosidase (1:500, Promega, Madison, WI), anti-GFP (1:400, Rockland Immunochemicals, Gilbertsville, PA), and Fasciclin 3 (clone 7G10, 1:10, Developmental Studies Hybridoma Bank) were used in this study.…”
Section: Immunohistochemistry and Tunel Detectionmentioning
confidence: 99%